Room-temperature direct-bandgap photoluminescence from strain-compensated Ge/SiGe multiple quantum wells on silicon - 胡炜玄 成步文 薛春来 张广泽 苏少坚 左玉华 王启明 (Chinese physics B, 2012)
Strain-compensated Ge/Si0.15Ge0.85 multiple quantum wells were grown on an Si0.1 Ge0.9 virtual substrate using ultrahigh vacuum chemical vapor deposition technology on an n＋-Si（001） substrate. Photoluminescence measurements were performed at room temperature, and the quantum confinement effect of the direct-bandgap transitions of a Ge quantum well was observed, which is in good agreement with the calculated results. The luminescence mechanism was discussed by recombination rate analysis and the temperature dependence of the luminescence spectrum.